Autonomous underwater vehicle Manoeuvrability studies - Yoong, Hou Pin; Yeo KB @ Abdul Noor; Choong, Wai Heng; Teo, Kenneth Tze Kin (Universiti Malaysia Sabah, 2010)
This research project is aimed to understanding the manoeuvrability of AUV and develop mathematical model to describe behaviour of vehicle interaction with the operating environment. A hovering type of AUV was defined base on the operation need of the AUV where it is likely to be applied in underwater research and exploring activities. Due to the increase demand of AUV, major efforts have been made in developing AUV in overcoming the challenging scientific and engineering problems caused by the unstructured ocean environment. The theoretical modeling of the AUV had being developed via Newtonian mechanics approach and the 6-DOF dynamic equations of motion are derived throughout the process. The governing equations mainly constitute terms of rigid body inertia matrix, hydrodynamic damping matrix, restoring forces and moments, environmental and propulsion forces and moments. Subsequently, a feasible 3-D solid modeling of the AUV had been designed through iterative method with CAD and CAE verification. Fluid interactions and manoeuvrability design analysis was achieved through implementation of CFD tool, COSMOSFloWorks. The theoretical modeling developed had been simplified under several relevant assumptions and the second order non-linear differential . equation solved using the programming software MA TI.AB to investigate the translational motion of the vehicle in the surging direction. The result from the model is the AUV motion relation, drag force and lift coefficient that could be utilized in the further AUV prototype development. The solid 3D design of the AUV had been achieved through spiral design process of iterative method. The method involves design statement, preliminary design, conceptual design and detailed design. Fundamental hydrodynamic knowledge had been applied to facilitate the design of the AUV. The optimum thruster location had been identified and the optimum design achieved. The scope of physical solid modeling had been effectively implemented via CAD software. SolidWorks licence by Universiti Malaysia Sabah had been utilized as the CAD platform in developing the AUV 3D model Stalling phenomena had also been identified as 15° through simulation software, COSMOSFloWorks. The stall pitching angle defines where the unstable manoeuvring of the vehicle will occur. COSMOSFloWorks also had been utilized to examine the effect of current velocities towards the AUV lift and drag coefficients. The simulation was conducted at various Reynolds number and various pitching angles. The investigation has found that the lift coefficient and drag coefficient increases as the pitching angle increases, but the considered range of Reynolds number had no significant effect on these hydrodynamic coefficients. These results were important for the design of better guidance and control systems for the AUV to achieve effective manoeuvring in current flow environment.